"I Have a Bag of Old Knickers. Do You?": Under-Worlding Our Underwear through Audio Found Poetry - Mendus, Alys (Art/Research International, 2023)
This article presents audio found poetry as an approach which positions participants’ voices in the heart of the inquiry. The methodology was influenced by radio autoethnography and audio papers where theory, voices, and sound are combined to create a new aural experience—an approach that argues that it is essential that the audience listens rather than reads. These two audio found poems share the voices of 14 participants from Australia, United Kingdom, North America, and Mainland Europe, interwoven with the author, talking about their relationship with underwear. Participants recorded their own story. Each voice was edited using Audacity (a software program) and then different voices were joined together. Two poems emerged. Audio 1: Practical Underwear shares stories from day-to-day underwear preferences and stories of those who do not wear underwear. The stories in Audio 2: Dress Code Red are connected to sexuality and political aspects of underwear. Framing the work through the lens of new materialism creates a space of agency for an entanglement between the underwear and the human voices speaking about it, which in turn affects the embodied experience of the listener. What stories could your underwear tell?